MADM Method for Flower Type Selection in Ornamental Plant Watering Based on Microcontroller and Solar Panels - Tijaniyah, Tijaniyah; Hidayatullah, Syarif; Fahlan, Nauval Sya'bani (Universitas Nurul Jadid, 2025)
This research aims to develop an automatic watering system based on a microcontroller and solar panels, using the Multi-Attribute Decision Making (MADM) method to determine the type of flower that is suitable for the watering system. Solar panels are used as the main energy source to increase the efficiency and sustainability of the system. The Multi-Attribute Decision Making ( MADM) method with the SAW technique uses the highest ranking calculation. The types of ornamental plants are Bougainvillea, Monstera, Peace Lily (Spathiphyllum) and pothos. The highest ranking for the type of flower is the monstera flower with a weight value of 11.95. With this system, ornamental plant owners can more easily determine plants and care for their plants without the need for regular manual watering. In addition, the use of solar panels makes this system more energy efficient and environmentally friendly. The owner of the flower shop really welcomed this control system tool because it can save Rp. 36,000 per month for electricity costs for watering ornamental plants because all power can be generated by solar panels, namely 250 Watts per day with a panel size of 120 WP. The total power usage of the ornamental plant watering control system is 35.25 Watts. Solar panels produce less power in the morning, at 9-10 watts, and 96-99 watts in the afternoon. During hot weather, solar panels produce more power